Comparative Study Of The Results Of Treatment With A Modern Modified Method Of Separating Lymph Nodes For Throat Cancer - Umid Sunnatovich, Mamedov; Lola Jakhonqulovna, Sultonova (Journal of Neonatal Surgery, 2025)
The results of studies conducted to date worldwide show that one of the most important prognostic signs of head and neck squamous cell carcinoma is the presence of metastases. Tumours of the oropharynx are complex anatomically and histologically because of the specificity for the detection of metastases in the thorax, computed tomography or magnetic resonance imaging of the chest is performed. In malignant tumours of head and neck organs spread locally, then metastasise to adjacent lymph nodes in the neck. Spread to local lymph nodes is partly related to tumour size, grade and aggressiveness.